Regioselective Synthesis, Antimicrobial Evaluation and QSAR Studies of Some 3‐Aryl‐1‐heteroarylindeno[1, 2‐c]pyrazol‐4(1H)‐ones. (23rd June 2016) - Mor, Satbir; Mohil, Rajni; Nagoria, Savita; Kumar, Ashwani; Lal, Kashmiri; Kumar, Devinder; Singh, Virender
Abstract : A series of seventeen 3‐aryl‐1‐heteroarylindeno[1, 2‐ c ]pyrazol‐4(1 H )‐ones (4a, 4b, 4c, 4d, 4e, 4f, 4g, 4h, 4i, 4j, 4k, 4l, 4m, 4n, 4o, 4p, 4q ) has been synthesized and characterized by spectral (IR, 1 H NMR, and mass), X‐ray crystallography and analytical results. All the indenopyrazoles (4a, 4b, 4c, 4d, 4e, 4f, 4g, 4h, 4i, 4j, 4k, 4l, 4m, 4n, 4o, 4p, 4q ) were tested for their in vitro antimicrobial activity against two Gram‐positive bacteria viz. Bacillus subtilis (MTCC 441) and Staphylococcus aureus (MTCC 7443), two Gram‐negative bacteria, viz. Escherichia coli (MTCC 42) and Pseudomonas aeruginosa (MTCC 741) and two fungi, viz. Candida albicans (MTCC 183) and Aspergillus niger (MTCC 282) using ceftriaxone and fluconazole as standard references against bacterial and fungal strains, respectively. Among the synthesized derivatives, 4f against B. subtilis and S. aureus, 4e against E. coli, 4g and4j against P. aeruginosa, 4k and4l against C. albicans, and4k against A. niger were found to exhibit appreciable antimicrobial activities. However, 4g (minimum inhibitory concentration, 0.0036 µmol/mL) was found to be more potent than the reference, that is, fluconazole (minimum inhibitory concentration, 0.0050 µmol/mL) against A. niger . Moreover, both antibacterial and antifungal activities were found to be prolific. The radial distribution function parameters were found to be important for description of activities against the modeled strains in quantitativestructure–activity relationship studies. Abstract :